INDEPENDENT COMMISSIONER, INSTITUTIONAL OWNERSHIP AND FINANCIAL DISTRESS BANKS IN INDONESIA - Isnalita, Isnalita; Utama, Anak Agung Gde Satia (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
This research aim to determine the effect of independent commissioner and institutional ownershipto financial distress banks in Indonesia. The existence of the banking crisis occurred in 1997/1998resulted the collapse of public confidence in banking industry. In 2008, the scale, pattern, anda different scope, we face the reality that seems similar to the condition of the banks in the endof 1997. Financial distress experienced is not only caused by external factors stemming fromthe bank but also can be caused by internal factors. On the other hand, the financial distress inthe banking sector can be caused by governance are not good in running the bankâ€™s operations.This study used a quantitative approach. The unit of analysis is the banks in Indonesia with dataobtained from directory of Bank Indonesia in 2008-2009. The research sampling techniques useÂ saturated sampling or census. Research design use multiple logistic regression with the crossÂ section. The result from this study indicated that independent commissioners and institutionalownership cannot prevent the financial distress in 2008 and 2009.